Social-environmental characteristics of community gardens in public housing neighbourhoods in Kuala Lumpur - Mohd Sharif, Shahida; Ujang, Norsidah; Abdul Shukor, Shureen Faris; Maruthaveeran, Sreetheran (Springer Nature, 2024)
Despite growing global interest, academic literature on community gardening remains sparse, especially for socio-economically marginalised populations. This also applies to Kuala Lumpur, where limited literature has explored socio-economically marginalised populations participating in community gardening. Building on this foundation, the study includes data collection and documentation in spatial databases to inform on the types of public housing in Kuala Lumpur and spaces utilised for community gardening. Identification of responsible associations and agencies, population density, median household income, land ownership, and how it affects community gardening initiatives are discussed. The methods used are interviews, site visits, research, government reports, and archives. Outputs include documentation and mapping of the community gardens using ArcGIS data. The examination shows that community gardens vary in size, activities, and gardening methods. The findings point to the need for more community gardens in high-rise public housing neighbourhoods, particularly those without balconies within their residential units. The map and database produced will help researchers, policymakers, and local authorities plan and develop more community gardens to support Kuala Lumpur's sustainability initiative.